Examination of Haematotoxicity of Fixed-Dose Highly Active Antiretroviral Drug in Albino Wistar Rats. (30th December 2012) - Nubila, Thomas; Ukaejiofo, Ernest O.; Nubila, Nkoyo I.; Okorie, Godfrey I.
Abstract : Highly active antiretroviral therapy (HAART) is considered toxic and has other life-threatening side effects. Our aim was to evaluate the haematotoxic effects of lamivudine, zidovudine, and nevirapine fixed-dose combinations in Albino Wistar rats. Fifty (50) three (3) months old male Albino Wistar rats weighing between 200 and 250 g were randomly assigned to five (5) groups (A, B, C, D, and E). Group A served as control. Two (2 mLs) of venous blood was aseptically collected on Days 5, 10, 15, 20, and 25 of treatment. Red blood cell (RBC) mean value recorded statistically significant increase (P < 0.05 ) in groups B and C when compared with the control group on Day 5. However, there was a statistically significant decrease (P < 0.05 ) in RBC, haemoglobin concentration (Hb), packed cell volume (PCV), and some red cell indices on Day 10. In addition there was no statistically significant difference (P > 0.05 ) in all the parameters evaluated when the test group was compared with the control on Day 25. Furthermore, there was a time-related statistically significant increase (P < 0.05 ) in the two major blood cells—RBC and platelet counts. From the result of this present study, it can be concluded that HAART when administered in fixed-dose combinations have no subacute haematotoxic effects.